Factors Related to the Incidence of Diarrhea of Children Aged 24-59 Months in Karangkamulyan Village, Cihara District, Lebak Regency in 2020 - Hafshah Farah Fadhilah; Kusharisupeni Djokosujono; Ratu Ayu Dewi Sartika (Indonesian Journal of Public Health Nutrition, 2023)
AbstractDiarrhea remains a major issue in developing countries, including Indonesia, and is a leading cause of malnutrition and death. Banten is one of the provinces with a high incidence of diarrhea. In 2019, the district with the highest number of diarrhea cases for all ages in Banten was Lebak with a total of 50,270 cases. The age group with the greatest number of diarrhea cases was toddlers with over 14,000 cases. This study aimed to investigate the relationship between the incidence of diarrhea and the characteristics of toddlers and their parents, personal hygiene, and environmental sanitation. The study used secondary data with a cross-sectional design and a sample size of 209 toddlers aged 24-59 months. The dependent variable was the incidence of diarrhea, while the independent variables were the child's age, gender, mother's education, mother's occupation, family income, hand washing habits, snacking habits, footwear habits when playing outside the home, nail cleanliness, and toilet habits, drinking water source, storage of clean water after cooking, and toilet ownership. The results of the bivariate analysis in this study showed that there was a relationship between the child's age (p-value = 0.001; OR = 2.990), the mother's education (p-value = 0.027; OR = 0.404), the mother's habit of washing hands with running water (p-value = 0.001; OR = 0.335), and the source of drinking water (p-value = 0.005; OR = 0.329) with the incidence of diarrhea in toddlers aged 24-59 months in Karangkamulyan Village, Cihara Sub-district, Lebak District, Banten Province in 2020. Keywords: Toddler, diarrhea, hand washing, drinking water source AbstrakPenyakit diare menjadi permasalahan utama di negara-negara berkembang termasuk di Indonesia, diare juga menjadi penyebab utama gizi kurang yang bisa menimbulkan kematian. Banten merupakan salah satu provinsi dengan angka kejadian diare yang tinggi. Sedangkan daerah Kabupaten / Kota di Provinsi Banten dengan kasus diare tertinggi untuk semua umur pada tahun 2019 adalah Kabupaten Lebak dengan total 50.270 kasus. Kelompok umur dengan jumlah kasus diare terbanyak adalah usia balita dengan total lebih dari 14.000 kasus. Penelitian bertujuan untuk mengetahui hubungan antara kejadian diare terhadap karakteristik anak balita dan orang tua, personal hygine, dan sanitasi lingkungan. Penelitian ini menggunakan data sekunder dengan desain cross-sectional dengan jumlah sampel sebanyak 209 anak balita usia 24-59 bulan. Dengan variabel dependen yaitu kejadian diare dan variabel independen yaitu usia anak, jenis kelamin anak, pendidikan ibu, pekerjaan ibu, penghasilan keluarga, kebiasaan mencuci tangan, kebiasaan jajan, Kebiasaan Pemakaian Alas Kaki saat bermain di luar rumah, kebersihan kuku, dan kebiasaan BABS, sumber air minum, penyimpanan air bersih setelah dimasak, dan kepemilikan jamban.  Hasil analisis bivariat pada penelitian ini menunjukkan bahwa adanya hubungan antara usia anak (p- value = 0,001; OR = 2,990), pendidikan ibu dengan (p- value = 0,027; OR = 0,404), kebiasaan ibu mencuci tangan dengan air mengalir (p- value = 0,001; OR = 0,335), dan sumber air minum (p- value = 0,005; OR = 0,329) dengan kejadian diare pada balita usia 24-59 bulan di Desa Karangkamulyan, Kecamatan Cihara, Kabupaten Lebak, Provinsi Banten tahun 2020. Kata kunci: Balita, diare, cuci tangan, sumber air minum